Branching fraction measurements of the color-suppressed decays B[bar]0 to D([ast])0π0, D([ast])0[eta], D([ast])0[omega], and D([ast])0[eta]' and measurement of the polarization in the decay B[bar]0 → D[ast]0[omega] - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We report updated branching fraction measurements of the color-suppressed decays ¯¯¯B0→D0π0, D*0π0, D0η, D*0η, D0ω, D*0ω, D0η′, and D*0η′. We measure the branching fractions (×10−4): B(¯¯¯B0→D0π0)=2.69±0.09±0.13, B(¯¯¯B0→D*0π0)=3.05±0.14±0.28, B(¯¯¯B0→D0η)=2.53±0.09±0.11, B(¯¯¯B0→D*0η)=2.69±0.14±0.23, B(¯¯¯B0→D0ω)=2.57±0.11±0.14, B(¯¯¯B0→D*0ω)=4.55±0.24±0.39, B(¯¯¯B0→D0η′)=1.48±0.13±0.07, and B(¯¯¯B0→D*0η′)=1.49±0.22±0.15. We also present the first measurement of the longitudinal polarization fraction of the decay channel D*0ω, fL=(66.5±4.7±1.5)%. In the above, the first uncertainty is statistical and the second is systematic. The results are based on a sample of (454±5)×106 B¯¯¯B pairs collected at the Υ(4S) resonance, with the BABAR detector at the PEP-II storage rings at SLAC. The measurements are the most precise determinations of these quantities from a single experiment. They are compared to theoretical predictions obtained by factorization, Soft Collinear Effective Theory (SCET) and perturbative QCD (pQCD). We find that the presence of final state interactions is favored and the measurements are in better agreement with SCET than with pQCD.
Im Titel ist das B mit einem Oberstrich versehen
Im Titel sind 0 und * hochgestellt
Im Titel sind [eta] und [omega] als griechische Buchstaben dargestellt und tiefgestellt
Im Titel ist [ast] als Tropfensternchen dargestellt
Gesehen am 12.08.2022